PROBLEMS IN THE IMPLEMENTATION OF AL-QURAN AND FARDU CLASS CLASSES PROGRAM (KAFA) IN KEDAH RIVER DISTRICT - Ruzaimah Zainol Abidin; Azman Md Zain; Mohd Hilmi Hamzah (Journal of Islamic, Social, Economics and Development, 2017)
The KAFA program is a low level religious education concept to support and strengthen the existing Islamic education in the implementation of National Education of Malaysia. The emphasis given in the program was in the aspect of Quranic reading skills with the fate and strengthening of the foundations of Fardu Ain among his students, including Arabic knowledge and writing Jawi. However, in the implementation of the KAFA Program, there are several problems that often occur. Through research on the KAFA program in the Pendang area, these problems are being identified. The design of the study uses face-to-face interviews with samples randomly selected among primary school teachers in the area. The findings show that the problems that often occur in the implementation of the KAFA program are due to the problems of management, teaching, discipline and teacher allowance. It is hoped that this problem can be addressed by the Islamic Education Coordination and Development Section, the Islamic Affairs Division (BAHEIS), the Prime Minister's Department (JPM), Kuala Lumpur and will further enhance the future of the program as the goal of KAFA's Islamic Education is to to produce students who are knowledgeable, believing, skillful, doing good deeds and being virtuous.